2015
DOI: 10.1186/s40364-015-0043-2
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide potentiates lung cancer cells to cisplatin-induced apoptosis by selectively inhibiting the NER activity

Abstract: BackgroundCisplatin and many other platinum-based compounds are important anticancer drugs that are used in treating many cancer types. The development of cisplatin-resistant cancer cells, however, quickly diminishes the effectiveness of these drugs and causes treatment failure. New strategies that reverse cancer cell drug resistance phenotype or sensitize cancer cells to these drugs, therefore, need to be explored in order to improve platinum drug-based cancer treatment. Triptolide is a bioactive ingredient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…This ability to block DNA repair has important implications for the anticancer activity of CDDP, which effectiveness has been shown to be enhanced by the combined treatment with triptolide (26). In agreement with that, experimental studies confirmed that low concentrations of triptolide were able to potentiate the CDDP activity in human lung cancer (27) and human bladder CDDP-resistant cells (28).…”
Section: Discussionsupporting
confidence: 64%
“…This ability to block DNA repair has important implications for the anticancer activity of CDDP, which effectiveness has been shown to be enhanced by the combined treatment with triptolide (26). In agreement with that, experimental studies confirmed that low concentrations of triptolide were able to potentiate the CDDP activity in human lung cancer (27) and human bladder CDDP-resistant cells (28).…”
Section: Discussionsupporting
confidence: 64%
“…The combined therapy of triptolide and 5-fluorouracil further promotes apoptosis and inhibits tumor growth through down-regulating vimentin in human pancreatic cancer AsPC-1 cells and AsPC-1 xenograft mice [453]. Besides, low concentration of triptolide potentiates cisplatin-induced apoptosis in human lung cancer HTB-182, A549 and CRL-5810 and CRL-5922 cells [454], and triptolide with cisplatin synergistically enhances apoptosis and induces cell cycle arrest in human bladder cancer cisplatin-resistant cells [409].…”
Section: Triptolidementioning
confidence: 98%
“…Platinum analogues induce DNA damage by binding to DNA in target cells, promoting apoptosis and leading to the anti-neoplastic activity [5-9]. One of the main mechanisms of platinum resistance is DNA repair [10].…”
Section: Introductionmentioning
confidence: 99%